Day case hemithyroidectomy is safe and feasible: experience in Scotland. Issue 4 (November 2015) - de Boisanger, Louis; Blackwell, Nicky; Magos, Tiarnan; Adamson, Richard; Hilmi, Omar
Background and aims: We aimed to analyse the safety and feasibility of day case hemithyroidectomy. Methods and results: We reviewed all hemithyroidectomies led by two surgeons across two sites between 2010 and the end of 2013. Patients were divided into 'planned inpatient' or 'planned day case'. Results: Day of discharge, conversion to inpatient procedure, intraoperative and postoperative complications and postoperative presentations or readmission to hospital were analysed. Age, gender, American Society of Anaesthesiologists score and indication for surgery were also recorded. One-hundred and eighty hemithyroidectomy cases were analysed, 35 (19.5%) were planned as inpatient procedures. Of the remaining 145 (80.5%) planned day case: 106 (73.1%) were successfully discharged on the same day and 39 (26.9%) were not; 11 (7.6%) were converted to inpatient procedures perioperatively; 8 (5.5%) had additional procedures; 6 (4.1%) had wound infections; 7 (4.8%) presented to ER; 1 (0.7%) of which required readmission to hospital for a reason unrelated to the surgery. None had laryngeal nerve palsy, compressive haematoma or symptomatic hypocalcaemia. Conclusion: This study showed that hemithyroidectomy by experienced surgeons can be performed safely as a day surgery. No 'planned day case patients' in this study developed laryngeal nerve palsy, compressive haematoma or symptomatic hypocalcaemia.